STUDY OF MILLING PROCESS AND ITS EFFECT ON VITAMIN B1 AND FOLIC ACID CONTENTS ON LOWLAND RICE PROMISING LINES - Indrasari, Siti Dewi; Ardhiyanti, Shinta Dewi; Abdullah, Buang (Indonesian Agency for Agricultural Research and Development - MOA, 2014)
Rice is an important source of vitamin B1 and folic acid, but cultivated rice cultivars contain low of these nutrient. Breeding program had been conducted and several advanced lines with a high vitamin B and folic acid contents were found. This research aimed to study the contents of vitamin B1 and folic acid in the brown rice and milled rice of fifteen promising lowland rice lines. Dried paddy (14% moisture content) were husked in the mini husker (Satake THU 35A) to obtain brown rice and milled rice by using abrasive-type mini polisher (Satake TM-05, 1,450 RPM for 2 minutes). Vitamin B1 and folic acid in the brown rice and milled rice were determined by using HPLC equipped with fluorescence detector for vitamin B1 and UV detector for folic acid. Four out of fifteen rice lines studied showed a unique characteristic of vitamin B1 content in the brown rice and milled rice. Rice lines which have highest vitamin B1 in the brown rice were B10267-4-PN-6-2-3-2-2-2-3-3-2 (3.03 mg 100 g-1), B10876H-MR-2 (2.13 mg 100 g-1), B10531E-KN-1-2-PN-1-4-2 (1.33 mg 100 g-1) and B12411E-RS*-1-2-1 (1.21 mg 100 g-1). However after milling, 43-92% of their vitamin B1 were lost; the least loss was observed in B12411E-RS*-1-2-1 (1.21 mg 100 g-1) which was only 4%. Three out of fifteen rice lines studied has highest folic acid in brown rice, i.e. BP400G-PN-12-3-6 (158.5 µg 100 g-1), B10876H-MR-2 (152.0 µg 100 g-1), and B11742-RS*-2-3-MR-5-5-1-Si-1-3 (100.0 µg 100 g-1). After milling the line B10876H-MR-2 had the highest folic acid content (52.0 µg 100 g-1), much higher than that of Ciherang variety as a control. This study indicates the importance of having a suitable milling instrument to minimize loss of vitamin B1 and folic acid. The study also suggests the importance of creating new rice cultivars that have high nutrient and resistant to milling process.